Erratum to: Search for direct pair production of scalar top quarks in the single- and dilepton channels in proton-proton collisions at ?s = 8 TeV (JHEP, (2016) 7, (027), 10.1007/JHEP07(2016)027) - The, C. M. S. collaboration; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; et al. (My University, 2016)
In the original paper, the wrong plot was used in figure 4. The corrected figure is given below. (Figure presented.). © 2016, The Author(s).
Citation: The, C. M. S. c., Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., . . . Woods, N. (2016). Erratum to: Search for direct pair production of scalar top quarks in the single- and dilepton channels in proton-proton collisions at ?s = 8 TeV (JHEP, (2016) 7, (027), 10.1007/JHEP07(2016)027). Journal of High Energy Physics, 2016(9). doi:10.1007/JHEP09(2016)056